Contribution on the understanding of EPB-TBM drives in complex geologic structures. (January 2021) - Acun, Sinan; Bilgin, Nuh; Erboylu, Ulaş
Highlights: Squeezing characteristics of complex weakness zones were studied. The effect of EPB pressure on reducing TBM jamming risk is explained. The methodology of salvation operations of jammed TBMs is explained. It is proved that foam in some cases is not best choice for jammed TBMs. Abstract: The studied area is a part of the New Istanbul Airport Metro construction project, which is on the Northwest of the city center towards the Black Sea Coast on the European Side of Istanbul. For this project ten EPB-TBMs were used. Two of them jammed/blocked consecutively within complex weakness zones as loose and open crushed zones. These zones have a complex geometry and structure filling with materials having very low strength characteristics. Squeezing occurred in both tubes of the first line. EPB-TBMs jammed three times in the first tube and once in the second tube. Apart from waiting time and using of lubricating agents, the effect of EPB pressure on reducing TBM jamming/blocking risk is explained. Mean EPB pressure applied in the second tube within studied chainages was 1.65 bar which was almost twice than the one used in the first tube (0.83 bar) making an increase in mean thrust force of 20% and increase in the mean torque values of 10% compared to ones obtained in the first tube. However, it is observed that higher EPB pressures helped stopping the collapses of loose materials within complex weakness zones. The methodology of salvation operations, mitigations measures as injecting bentonite, polymers and using additional cylinders are discussed within the paper and it is believed that the results will serve as basis to understand better the squeezing mechanism of such complex structures and to help to take correct mitigation measures in future EPB-TBM drives. In complex geologies in similar weakness zones it is proved that foam lubricants are not best choices and additional thrust cylinders are a necessity.